2013
DOI: 10.1002/pssa.201329349
|View full text |Cite
|
Sign up to set email alerts
|

Cuprous iodide - a p-type transparent semiconductor: history and novel applications

Abstract: Halide semiconductors stand at the very beginning of semiconductor science and technology. CuI was reported as the first transparent conductor, and the first field effect transistor was made from KBr. Although halogens are frequently used in semiconductor preparation, little use is currently made from halide semiconductors in electronics and photonics. We review past reports on the metal halide semiconductor CuI and related alloys and discuss recent progress with regard to this material including its use in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
323
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 253 publications
(357 citation statements)
references
References 293 publications
(334 reference statements)
26
323
1
7
Order By: Relevance
“…The quality of the films that we have produced on amorphous glass through a simple, easy and cheap method is similar to the quality of the ones that Kosta et al have produced through electrochemical method on a crystalline structure; a similar type of surface can be seen in Figure 7a. Grundman et al, who showed that they have produced the most regular structure through SEM images, have captured particle structures similar to triangular prism, as can be seen in our SEM images 19 . Bu all these researchers have attempted to growth crystalline film on crystal substrates using devices.…”
supporting
confidence: 67%
“…The quality of the films that we have produced on amorphous glass through a simple, easy and cheap method is similar to the quality of the ones that Kosta et al have produced through electrochemical method on a crystalline structure; a similar type of surface can be seen in Figure 7a. Grundman et al, who showed that they have produced the most regular structure through SEM images, have captured particle structures similar to triangular prism, as can be seen in our SEM images 19 . Bu all these researchers have attempted to growth crystalline film on crystal substrates using devices.…”
supporting
confidence: 67%
“…Considering the fact that the obtained CuI films are in the polycrystalline state, further improvement in the hole , other p-type (black circles), and n-type TCs (blue squares). P-type TCs: SrCrO (19), CuCrMgO (18), CaCoO (46), CuScO (10), LaSrCrO (19), CuYCaO (11), ZnRhO (47), AgCoO (45), MgGaN (6,43), MgCrO (48), CuAlO (44), SrCuO (12), CuGaO (8), ZnON (49), iodi-CuI (prepared by iodization) (36), sput-CuI (prepared by sputtering) (29), evap-CuI (prepared by thermal evaporation) (27), and PLD-CuI (prepared by PLD) (28). The superscripts of p-type TCs indicate the FOM.…”
Section: Resultsmentioning
confidence: 99%
“…However, the performance of CuI as a highly conducting p-type TC has not been well explored, because it is commonly recognized as a nondegenerate semiconductor with a roomtemperature conductivity limited to values below 100 S/cm (27). In contrast, conventional n-type TCs are usually degenerate semiconductors, such as indium tin oxide, which act as metallic conductors with conductivity above 10 3 S/cm.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…The most common route is the chemical reaction of Cu thin films with vapor-phase iodine (known as the vapor iodination method), 8,21,[24][25][26] a Cu film is quickly converted to a polycrystalline γ-CuI film upon exposure to iodine vapor. The resulting polycrystalline γ-CuI films exhibit semiconducting properties, with hole densities of 10 18 -10 19 cm -3 and hole mobilities of 1-10 cm 2 V -1 s -1 .…”
mentioning
confidence: 99%